2012
DOI: 10.2337/dc11-1623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electronegative VLDL on Endothelium Damage in Metabolic Syndrome

Abstract: OBJECTIVEBiochemical heterogeneity governs functional disparities among lipoproteins. We examined charge-defined VLDL subfractions in metabolic syndrome (MetS) to determine whether their increased electronegativity is associated with increased cytotoxicity and whether high concentrations of highly electronegative subfractions render VLDL harmful to the vascular endothelium.RESEARCH DESIGN AND METHODSPlasma VLDL of normal individuals (control subjects) (n = 13) and of those with MetS (n = 13) was resolved into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Patients with MetS or type 2 diabetes often have increased plasma levels of TG and TG-derived very low density lipoproteins (VLDL) [ 15 , 16 ]. We previously showed that a negatively charged subfraction of VLDL in MetS patients was most toxic to human vascular endothelial cells and that the negatively charged VLDL was richer in MetS than healthy controls [ 17 ]. Moreover, VLDL from patients with AF is more highly glycated and more oxidized [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with MetS or type 2 diabetes often have increased plasma levels of TG and TG-derived very low density lipoproteins (VLDL) [ 15 , 16 ]. We previously showed that a negatively charged subfraction of VLDL in MetS patients was most toxic to human vascular endothelial cells and that the negatively charged VLDL was richer in MetS than healthy controls [ 17 ]. Moreover, VLDL from patients with AF is more highly glycated and more oxidized [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adiels et al [39] and Gill et al [40] reported that in patients with metabolic syndrome or type 2 diabetes, insulin-resistant states and the loss of insulin-mediated suppression of apoB100 secretion lead to increased production of large VLDL-1 particles. Hypersecretion of large VLDL-1 particles, which contain more cholesterol, results in higher levels of remnant particles and small dense LDLs and lower levels of HDL that may contribute to the progression of vascular endothelial injury and atherosclerosis [41-43]. In peritoneal dialysis, glucose absorption and protein loss from the dialysate further aggravate the metabolic abnormalities and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…From evaluating individuals with and without MetS, our colleagues reported the diversity of VLDLs, in which VLDL of MetS carries a more negative charge and is significantly cytotoxic to human vascular endothelial cells when compared with VLDL of non-MetS subjects [80]. Later we showed that VLDL of MetS patients induced cytosolic oxidative stress and exhibited more cytotoxicity to atrial myocytes (HL-1 cells) compared with VLDL of non-MetS subjects [81].…”
Section: Vldl Of Mets Exhibits Cytotoxicity To Atrial Myocytesmentioning
confidence: 95%